Dinamika Spasial Harga Telur Ayam Ras Di Indonesia: Analisis Koefisien Variasi Dan Structural Break (Jurnal Agribisnis Indonesia, 2026)
Price fluctuation is one of many issues in strategic commodities with high consumption levels, such as broiler eggs. A wide range of challenges is faced by the stakeholders to maintain the price stability. This article analyzes the price dynamics of broiler eggs in Indonesia and identify structural breaks in daily price data from January 2020 to November 2024. Price dynamics are analyzed using the coefficient of variation (CV) method while structural breaks use the Augmented Dickey-Fuller test. The study highlights the different patterns of price variation at four distribution levels-producers, wholesalers, traditional markets, and modern markets-and analyzes the impact of structural breaks on price stability. The results show that modern markets, wholesalers, and producers have low price variations (